PELATIHAN DESAIN LABEL PRODUK UNTUK MENINGKATKAN KOMPETENSI MAHASISWA UKM KEWIRAUSAHAAN UNWAHA JOMBANG - Dinaloni, Diah; Muktiadji, Henky; Anggreini S, Apprilia; Kurniawan, Dandy (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Product label design is a consideration for consumers when purchasing products, besides that, an anttractive product label design is not only a visual attraction, but it is also the key to differentiating the product from its competitors. The aim of this PkM is to provide training in making product label designs to improve the competency of UNWAHA Jombang Entrepreneurship UKM students.  The PkM implementation method consists of: (1) Preparation stage to prepare the training module, location to be the training venue, and training implementation schedule(2) The implementation stage is carried out to explain the training module that has been prepared, then the training participants are given the opportunity to ask questions directly about things they do not understand, and then the training participants are given the opportunity to practice making product label designs directly guided and assisted by the team. PkM; (3) The evaluation stage is carried out by providing feedback and design corrections to the product label designs that have been made by the training participants, then based on the questionnaire analysis, it can be seen that there are a number of positive changes in the participants' perceptions and skills after participating in the product label design training using CorelDRAW software, so that PkM activities are said to run smoothly in accordance with the aim of increasing the competency of UNWAHA Jombang Entrepreneurship UKM students